Fatherless Representation of Children's Empathy and Creativity Development in Selected Cartoon Series on Youtube - Celvin Reindira Alfiani; Ari Ambarwati (EDUTEC : Journal of Education And Technology, 2024)
This study aims to examine the issue of fatherlessness in three selected cartoon series on YouTube, including the Upin and Ipin, Masha and The Bear and Pada Zaman Dahulu cartoon series to develop children's empathy and creativity. The study of fatherless cartoon series is important because the issue of fatherless in the last five years has surfaced because it is alleged that some Indonesian children have lost a father figure. So this research is important to provide an in-depth understanding of the fatherless issue. This research is included in descriptive qualitative research. The research data used is in the form of transcribed dialogues from the three cartoon series and interview dialogues. The data sources in this study are three fatherless cartoon series entitled Upin and Ipin, Masha and The Bear and Pada Zaman Dahulu, the storylines of the three fatherlees cartoon series, characterisation and high and low grade children. The data collection techniques used by researchers are listening techniques, note-taking techniques and interviews. Data analysis techniques used by researchers are observing three cartoon series on YouTube, interpreting, identifying, classifying, analysing and concluding. The results of this study show that there is creativity and empathy from the three fatherless-themed cartoon series. The main character is described as having social sensitivity, independence, and resilience in facing problems without the presence of a father figure. The three fatherless-themed cartoon series are able to form characters with high creativity and empathy, so as to inspire the audience to develop creativity and empathy in everyday life. This research can also be a foundation for further research on fatherlees-themed cartoons.